ANALISIS PERBANDINGAN KINERJA KEUANGAN PADA PT. ADARO ENERGI INDONESIA TBK DAN PT. BAYAN RESOURCES TBK. PERIODE 2020 – 2022 - Rasli; Rati Pundissing; Mince Batara (Jurnal Penelitian Multidisiplin, 2023)
This study aims to determine whether there are differences in financial performance at PT. Adaro Energi Indonesia Tbk, and PT. Bayan Resources Tbk in Indonesia. This type of research is a comparative quantitative research using a comparison design of two means of two independent populations. The analysis technique used in this study is the two-mean different test (independent sample test). The results of this study prove that there is no significant difference in each of the financial ratios at pt. Adaro Energi Indonesia Tbk, and PT. Bayan Resources Tbk.